The exerkine apelin reverses age-associated sarcopenia - Vinel, Claire; Lukjanenko, Laura; Batut, Aurelie; Deleruyelle, Simon; Pradère, Jean-Philippe; Le Gonidec, Sophie; Dortignac, Alizée; Geoffre, Nancy; Pereira, Ophelie; Karaz, Sonia; Lee, Umji; Camus, Mylène; et al. (Nature Medicine, 2018)
Sarcopenia, the degenerative loss of skeletal muscle mass, quality and strength, lacks early diagnostic tools and new therapeutic strategies to prevent the frailty-to-disability transition often responsible for the medical institutionalization of elderly individuals. Herein we report that production of the endogenous peptide apelin, induced by muscle contraction, is reduced in an age-dependent manner in humans and rodents and is positively associated with the beneficial effects of exercise in older persons. Mice deficient in either apelin or its receptor (APLNR) presented dramatic alterations in muscle function with increasing age. Various strategies that restored apelin signaling during aging further demonstrated that this peptide considerably enhanced muscle function by triggering mitochondriogenesis, autophagy and anti-inflammatory pathways in myofibers as well as enhancing the regenerative capacity by targeting muscle stem cells. Taken together, these findings revealed positive regulatory feedback between physical activity, apelin and muscle function and identified apelin both as a tool for diagnosis of early sarcopenia and as the target of an innovative pharmacological strategy to prevent age-associated muscle weakness and restore physical autonomy. The muscle-secreted, exercise-induced peptide hormone apelin decreases with aging and sarcopenia, and its repletion in aged mice with recombinant protein improves muscle mass and function.